Sexual dimorphism among species of Aleurocanthus Quaintance & Baker (Hemiptera: Aleyrodidae) in Taiwan, with one new species and an identification key - Dubey, Anil Kumar; Ko, Chiun-Cheng (Zootaxa, 2012)
Sexual dimorphism is recorded among the puparia of six species of Aleurocanthus from Taiwan, including Aleurocanthuslauriphaga sp.n. from Cinnamomum osmophloeum. A key is provided to the puparia of seven species of this genus knownfrom Taiwan, with illustrations of immature stages and the adult male and female of the new species. The flocculent waxsecretion pattern in the puparia of this new species is atypical amongst Aleurocanthus species. Newly recorded from Tai-wan is A. citriperdus Quaintance & Baker, and the record of A. spinosus (Kuwana) from Taiwan is discussed. A list of recorded host plants of Aleurocanthus species from Taiwan is provided.